Performance of short duration pulses with African winterthorn (Faidherbia albida) in semi-arid regions - GORKAR, G R; PRATIBHA, G (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 2 years (1995-96) on a red loamy sand soil at Hyderabad to evaluate theperformance of short duration pulses, viz. greengram (Phaseolus radiatus L.), blackgram (Phaseolus mungo L.) andcowpea (Vigna unguiculata L.) iritercropped with African winterthorn (Faidherbia albida Del.) trees at 2 densities, viz625 and 156 plants/ha. The results indicated that seeds yields of greengram and blackgram were higher under low treedensity (156 trees/ha) than that in sole and under high tree density, whereas cowpea seed yield were lower under the treesat both the densities compared to the sale cropping. The equivalent yield and net monetary returns were higher withblackgram under low tree density, followed by greengram. Soil fertility improved with trees. The tree diameter at breastheight was better in the lower tree density. The results clearly indicate that short duration legumes can be successfullyintercropped with F. albida at low tree densities.